Transformasi Hard Skill Menuju Soft Skill dalam Kurikulum dan Impelentasinya dalam Pembelajaran PAI - Kasmiati; Amril M (Lembaga Anotero Scientific Pekanbaru, 2025)
The purpose of this study is to see the transformation of hard skills and soft skills in the curculum and its implementation in PAI learning. This study uses a qualitative approach with the literature method. The results of this study indicate the transformation of hard skills and soft skills from the 2013 curriculum that developed hard skills, quite individual learning and passive students, as well as the highest achieving minimum completeness in the form of numbers or scores, became an independent curriculum whose main development was based on soft skills, learning Active, prioritizing teamwork, collaboration and mutual cooperation, and oriented to the results in the form of creative and innovative works of students. Curriculum transformation is carried out with the aim of creating the quality of human resources that are character and have essential competencies to become lifelong learners and are able to contribute to modern, democratic, and plural society. Curriculum transformation has an impact on PAI teacher competence which initially carried out conventional learning, and was dominant in strengthening students 'hard skills, developed into digital -based learning that was strengthened by information technology, and the main orientation of developing students' soft skills through the Pancasila Student Profile. The teacher can implement the dimensions of the Pancasila Youth Profile in PAI learning in 3 ways 1) Integrate the dimensions of Pancasila Student Profile in PAI subjects through intarakuricular activities, 2) As a teaching strategy used by the teacher or as a direct experience, 3) as a project of curricular activities. Achievement of the objectives of the independent curriculum must focus on increasing the soft skills of teachers in various forms of activities such as workshops, training, seminars, and further education. It aims to create a generation of noble and cultured character in the midst of unlimited technological attacks.